A chromosome-scale genome assembly of the tomato pathogen Cladosporium fulvum reveals a compartmentalized genome architecture and the presence of a dispensable chromosome. Issue 4 (26th April 2022) - Zaccaron, Alex Z.; Chen, Li-Hung; Samaras, Anastasios; Stergiopoulos, Ioannis
Abstract : Cladosporium fulvum is a fungal pathogen that causes leaf mould of tomato. The reference genome of this pathogen was released in 2012 but its high repetitive DNA content prevented a contiguous assembly and further prohibited the analysis of its genome architecture. In this study, we combined third generation sequencing technology with the Hi-C chromatin conformation capture technique, to produce a high-quality and near complete genome assembly and gene annotation of a Race 5 isolate of C. fulvum . The resulting genome assembly contained 67.17 Mb organized into 14 chromosomes (Chr1-to-Chr14), all of which were assembled telomere-to-telomere. The smallest of the chromosomes, Chr14, is only 460 kb in size and contains 25 genes that all encode hypothetical proteins. Notably, PCR assays revealed that Chr14 was absent in 19 out of 24 isolates of a world-wide collection of C. fulvum, indicating that Chr14 is dispensable. Thus, C. fulvum is currently the second species of Capnodiales shown to harbour dispensable chromosomes. The genome of C. fulvum Race 5 is 49.7 % repetitive and contains 14 690 predicted genes with an estimated completeness of 98.9%, currently one of the highest among the Capnodiales. Genome structure analysis revealed a compartmentalized architecture composed of gene-dense and repeat-poor regions interspersed with gene-sparse and repeat-rich regions. Nearly 39.2 % of the C. fulvum Race 5 genome is affected by Repeat-Induced Point (RIP) mutations and evidence of RIP leakage toward non-repetitive regions was observed in all chromosomes, indicating the RIP plays an important role in the evolution of this pathogen. Finally, 345 genes encoding candidate effectors were identified in C. fulvum Race 5, with a significant enrichment of their location in gene-sparse regions, in accordance with the 'two-speed genome' model of evolution. Overall, the new reference genome of C. fulvum presents several notable features and is a valuable resource for studies in plant pathogens.